EVALUATION OF THE STATISTICAL SIGNIFICANCE OF COMPACTIVE EFFORTS, SLAG AND CEMENT ON THE GEOTECHNICAL FEATURES OF LATERITE SOIL - SOLOMON IDOWU ADEDOKUN; AKINDELE CHRISTOPHER APATA; ADEWALE OLUKAYODE OGUNDALU; JOHNSON ROTIMI OLUREMI; ADESOKAN OYINLOLA; OLUKEMI KEHINDE FAGBENRO; OSEPH ADEBAYO IGE; ABOSEDE OLUFUNMI ADEWOYE (Journal of Engineering Studies and Research)
This study investigated the statistical significance of compactive efforts, steel slag and cement on the geotechnical features of the laterite soil. Steel slag and cement were incorporated into the soil. Some geotechnical tests were performed on slag-cement-soil samples. Findings showed that the liquid limit (LL) and plasticity index (PI) decreased with increasing slag content, while cement addition increased LL and PI. As compactive efforts increased, MDD and CBR increased with a corresponding decrease in OMC. A more significant influence of the compactive effort and steel slag on the geotechnical features of the laterite than that of cement was observed.